The teacher and the school curriculum - Fernando, Madeline T.; Oamil, Erwin L. (Mandaluyong City, 2022)
THE TEACHER AND THE SCHOOL CURRICULUM is a resource instructional material in module form. It corresponds with the content of the PPST based syllabus for the course as prescribed in CMO 30-s. 2017. This resource material consists of four modules composed of lessons. Each lesson follows a distinct format represented by the acronym GEAR UP. Gear-up means to prepare or equip oneself for something or to get ready. Thus, this material will equip the pre-service teachers with the fundamental concepts and principles in curriculum and curriculum development, to nake them ready to become curriculum planners, designers, implementers nd evaluators.
Keywords: Education-Curricula; Educational planning